The determinants of students' return intentions: A partial proportional odds model - Jan-Jan Soon (Journal of Choice Modelling, 2010)
This paper examines the determinants of foreign students' nonreturn intention to their home countries following completion of their study abroad. Such students' nonreturn is a type of brain drain. Survey data on the return intention of foreign students studying in tertiary-level courses in New Zealand universities are analyzed using a partial proportional odds model. This model takes into account the ordinal nature of the return intention as the dependent variable while at the same time allowing for possible violation of the parallel lines assumption from the explanatory variables. Perceptions of different aspects of one's home country, particularly the aspect of skill use opportunities, are generally found to have larger impacts on return intention than demographic, education-related, and sociocultural-related factors. Based on the results, the paper discusses some relevant policy implications.
Keywords: 330; foreign students' nonreturn/migration; brain drain; partial proportional odds model; return intention